The Sleep-Modulating Peptide Cortistatin Augments the h-Current in Hippocampal Neurons - Schweitzer, Paul (J Neurosci, 2003)
Cortistatin (CST) is a sleep-modulating peptide found exclusively in the brain. Although CST is closely related to somatostatin (SST) and binds to SST receptors, CST has effects on sleep and neuronal activity in cortex and hippocampus that differ from SST. To uncover the cellular mechanisms affected by CST, we studied the electrophysiological postsynaptic effects of CST and assessed its interaction with SST on hippocampal CA1 pyramidal neurons. CST altered intrinsic membrane properties and occluded SST effects, indicating that both peptides similarly augment the sustained K(+) M- and leak-currents (I(M) and I(K(L))). In the presence of SST, however, CST elicited an additional inwardly rectifying component in the hyperpolarized range. This effect was unaffected by barium, used to block K(+) currents, but was completely prevented by the selective h-current (I(h)) blocker ZD7288. CST, but not SST, selectively increased I(h) in a concentration-dependent manner by augmenting its maximum conductance. CST did not shift the I(h) activation curve, and the peptide effect was unaffected by a membrane-permeable analog of cAMP. We conclude that CST and SST similarly increase K(+) conductances in hippocampal neurons, most likely by activating SST receptors. However, CST additionally augments I(h), a voltage-dependent current that plays a key role in the modulation of synaptic integration and regulates oscillatory activity. Our results indicate that CST targets a specific conductance unaffected by SST to modulate cellular mechanisms implicated in sleep regulation.